Newborn with congenital salivary gland anlage tumor presenting with respiratory distress. Issue 3 (September 2015) - Swayampakula, Anil Kumar; Ischander, Mariam; Zuppan, Craig W.; Krishnan, Miguel; Tong, Karen; Qureshi, Sonea
Abstract: Breathing difficulty is a common complaint in the newborn period. Common etiologies range from infections to anatomic obstruction. Nasopharyngeal obstruction due to tumor is a rare cause of neonatal respiratory distress. We herein report a newborn presenting with respiratory distress due to a rare salivary gland tumor in the nasopharynx.